2022
DOI: 10.1155/2022/7666615
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Physical Education Teaching Tracking System Based on Multimedia Data Analysis and Artificial Intelligence

Abstract: The education system begins a significant dimension characterized by continuous improvement and impacted by technology, society, and cultural developments. This pattern shows the need to enhance physical and athletic scientific training methods. To make the teacher’s role more successful is the usage of computer systems and other computing infrastructure. This article aims to show the use of Information and Communication Technology (ICT) in the national association for physical education. The digitalization co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…Feng Cao et al [28] introduce the physical education tracking system (IPETS) and investigate the methods for formative athletic knowledge assessment in computer evaluation, because the educational system is always changing by technological, social, and cultural advances. The use of Information and Communication Technology (ICT) is critical for improving physical and athletic training approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Feng Cao et al [28] introduce the physical education tracking system (IPETS) and investigate the methods for formative athletic knowledge assessment in computer evaluation, because the educational system is always changing by technological, social, and cultural advances. The use of Information and Communication Technology (ICT) is critical for improving physical and athletic training approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The simultaneous improvement of sound and animation strongly stimulates the students' hearing, vision, and dynamic feeling (Li et al, 2021). At the same time, it can stimulate students' interest and attract their attention, so that students' memory of basic knowledge, basic technique, and basic actions can quickly enter short-term memory from instantaneous memory (Cao et al, 2022). The application of multimedia techniques in the teaching of PE in universities can carry out multi-angle and all-round analysis.…”
Section: Necessity Of Multimedia Technique In College Pementioning
confidence: 99%
“…By overlaying digital visualizations onto the user's physical environment, AREMS enhances the learning experience by offering interactive guidance and corrective cues in real time (Omarov et al, 2023). The effectiveness of AREMS as an instructional tool in physical education has been the subject of growing interest among researchers and educators (Cao et al, 2022). Previous studies have demonstrated the potential of AREMS to improve exercise technique, increase motivation, and reduce the risk of injury among users (Abulibdeh, et al, 2024;Rodriguez-Fuentes et al, 2024).…”
Section: Introductionmentioning
confidence: 99%